Molecular Biology and Diversification of Human Retroviruses - Meissner, Morgan E.; Talledge, Nathaniel; Mansky, Louis M. (Frontiers in Virology, 2022)
Studies of retroviruses have led to many extraordinary discoveries that have advanced our understanding of not only human diseases, but also molecular biology as a whole. The most recognizable human retrovirus, human immunodeficiency virus type 1 (HIV-1), is the causative agent of the global AIDS epidemic and has been extensively studied. Other human retroviruses, such as human immunodeficiency virus type 2 (HIV-2) and human T-cell leukemia virus type 1 (HTLV-1), have received less attention, and many of the assumptions about the replication and biology of these viruses are based on knowledge of HIV-1. Existing comparative studies on human retroviruses, however, have revealed that key differences between these viruses exist that affect evolution, diversification, and potentially pathogenicity. In this review, we examine current insights on disparities in the replication of pathogenic human retroviruses, with a particular focus on the determinants of structural and genetic diversity amongst HIVs and HTLV.